Polymorphism of the Growth Hormone Gene and its Association with Growth Traits in Ongole Grade Crossed with Simmental Cattle - Mu’in, MA; Astuti, M; Muladno, Muladno; Murti, TW; Artama, WT (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2007)
The present study was conducted to detect polymorphism of growth hormone (GH) gene in Ongole grade crossed with Simmental bull (SIMPO) and its association with growth traits. Blood samples of 62 cattle were taken from population of SIMPO cattle were located in the sub-province region of Bantul, Special Region of Yogyakarta. A 211 bp fragment of GH gene spanning from the forth intron region (49 bp) to fifth of exon (162 bp) was amplified and digested with AluI restriction enzyme to identified polymorphism at this locus. The resulted indicated that two genotypes LL and LV were found at the GH gene in SIMPO population cattle. The frequencies of L and V alleles were 0.82 and 0.18, respectively. In SIMPO calves, the average birth weight, 2 months body weight and daily body weight gains of LV genotypes were tend to higher than that of LL genotypes. (Animal Production 9(2): 53-58 (2007)Â Key Words : Gene, growth hormone, polymorphism, cattle, SIMPO